Diagnostic Accuracy of Fine Needle Aspiration Cytology in Salivary Gland Lesions: A Comparative Study with Histopathology as the Reference Standard at Bahawal Victoria Hospital, Bahawalpur, Pakistan: Fine Needle Aspiration Cytology for Diagnosing Salivary Gland Lesions - Afzal, Asmah; Shaheen, Uzma; Khalid, Fatima; Iqbal, Firdous; Akhtar, Azra (Pakistan Journal of Health Sciences, 2025)
Fine-needle aspiration cytology (FNAC) is one of the most widely used diagnostic tools for evaluating salivary gland lesions. However, its diagnostic accuracy is uncertain due to certain factors. Objective: To analyze the diagnostic accuracy of FNAC in salivary gland lesions compared to histopathological examination in a clinical setting. Methods: This cross-sectional study was conducted from October 2021 to June 2022 at Bahawal Victoria Hospital, Bahawalpur, Pakistan. A total of 75 patients, aged 18 to 75 years, were included in the study who were previously clinically diagnosed with salivary gland lesions. Every patient included in the study underwent the FNAC, and the outcomes were compared to the histopathological analysis of the excised biopsies. The results are analyzed in terms of sensitivity, specificity, NPV, PPV, and diagnostic accuracy. Results: Among the 75 patients, the mean age was 42.5 ± 14.3 years, with a male-to-female ratio of 1:1.08. FNAC results showed 7 non-neoplastic lesions (9.3%), 61 benign (81.3%), and 7 malignant neoplasms (9.3%). A histopathological analysis identified 63 benign, 5 malignant, and 7 non-neoplastic neoplasms. FNAC showed a 96.0% overall diagnostic accuracy, with sensitivity, specificity, Positive predictive value (PPV), and Negative Predictive Value (NPV) of 97.0%, 88.9%,98.5%, and 80.0% respectively. Two false-negative instances (2.7%) and one false-positive case (1.3%) were found in the study. Conclusion: FNAC is an extremely sensitive and accurate diagnostic tool especially when it is required to distinguish between benign and malignant neoplasms. However, its low specificity increases the risk of false-negative results where histopathological confirmation becomes an integral part of the diagnosis especially the cases where clinical suspicions are high.